Physiology of rumen bacteria associated with low methane emitting sheep : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Microbiology and Genetics at Massey University, Palmerston North, New Zealand - Kumar, Sandeep (2017, 2017)
The fermentation of feed and formation of methane (CH4) by ruminant animals occur in the rumen, and both are microbial processes. There is a natural variation in CH4 emissions among sheep, and this variation is heritable. Therefore, breeding for sheep that naturally produce less CH4 is a viable strategy to reduce anthropogenic greenhouse gas emissions. Rumen bacteria play a major role in feed fermentation and in the formation of hydrogen (H2) or formate, which are converted to CH4 by other rumen microbes called methanogens. It has been shown that rumen bacterial community compositions in low CH4 emitting sheep differ to those in high CH4 emitting sheep. This led to the hypothesis that the metabolism of dominant rumen bacteria associated with low CH4 emitting sheep should explain the lower CH4 yield, for example by producing less H2 or formate than bacteria associated with high CH4 emitting sheep. In this project, the diversity and physiology of members of the bacterial genera Quinella, Sharpea and Kandleria, which are major bacterial groups associated with low-CH4 emitting sheep, were investigated. It appeared that the genus Quinella is more diverse than previously suspected, and might contain at least eight potential species, although to date none have been maintained in laboratory culture. Sharpea and Kandleria contain two and one species respectively. Experiments with Sharpea and Kandleria showed that these behave like classical lactic acid bacteria that produce lactate as their major end product and did not change their fermentation pattern to produce more H2 or formate when grown in the presence of methanogens. This strengthens a previous hypothesis that sought to explain low CH4 emissions from sheep with Sharpea and Kandleria in their rumens, in which this invariant production of lactate was a key assumption. Quinella is another bacterium found in larger numbers in the rumen of some low CH4 sheep. Virtually nothing is known about its metabolism. FISH probes and cell concentration methods were developed which helped in its identification and resulted in construction of four genome bins of Quinella that were more than 90% complete with as little as 0.20% contaminated. Bioinformatic analyses of the proteins encoded by these genomes showed that Quinella has the enzymes for lactate formation and for the randomising pathway of propionate formation. This indicated that lactate and propionate might be major fermentation end products of Quinella. Additionally, the presence of an uptake hydrogenase in the Quinella genomes opens up the new possibility that Quinella might even use free H2 in the rumen. In all these possible pathways, little or no H2 would be produced, explaining why an increased abundance of Quinella in the rumen would lead to lower CH4 emissions from those sheep with high abundances of this bacterium.
Figures 1.1 & A6.1 used with permission
Keywords: Rumen; Microbiology; Sheep; Physiology; Methane; Metabolism; Research Subject Categories::NATURAL SCIENCES::Biology::Organism biology::Microbiology